CO2 capture based on Al2O3 ceramic membrane with hydrophobic modification. Issue 8 (July 2023) - Fu, Hongming; Xue, Kaili; Yang, Jihao; Li, Zhaohao; Zhang, Heng; Gao, Dan; Chen, Haiping
Abstract: In this paper, Al2 O3 ceramic membrane is modified to hydrophobicity by grafting 1 H, 1 H, 2 H, 2 H-perfluorodecyltriethoxysilane. And its properties are characterized in detail. CO2 capture performance of ceramic membrane is investigated by experiments. Results show that wetting resistance after modification is significantly improved, and contact angle increases from the initial 49.8–130.9°. However, hydrophobic modification has no significant effect on the crystalline phase, surface morphology and pore size distribution of the ceramic membrane. With ethanolamine (MEA) as absorbent, CO2 mass transfer rate and capture efficiency using modified hydrophobic ceramic membrane are 46.6 × 10 −3 mol/(m 2 ·s) and 98.0%, showing significantly increase compared to the original membrane. After 72 h immersion in MEA solution, quality of ceramic membrane does not change significantly. And there is almost no change in average pore size. We believe this study will provide a reference for the industrial application for CO2 capture by gas-liquid membrane contactor with ceramic membrane.